2017
DOI: 10.1186/s12939-017-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and finances: baseline characteristics of low income daily smokers in the FISCALS cohort

Abstract: BackgroundFinancial stress is a barrier to successful smoking cessation and a key predictor of relapse. Little is known about the financial situation of low-income Australian daily smokers. This study aims to describe and investigate associations between the financial functioning, tobacco use and quitting behaviours of low income daily smokers.MethodsLow-income Australian adult smokers in the ‘Financial Intervention for Smoking Cessation Among Low-income Smokers (FISCALS) randomised clinical trial completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…This study also revealed that individuals with low salary were mild smokers. Although many other studies [29][30][31] are inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…This study also revealed that individuals with low salary were mild smokers. Although many other studies [29][30][31] are inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar trend was observed in this study as participants who never attempted to quit showed a strong inclination towards both alcohol frequency and duration. Martire et al (17) reported that smoking though create financial stress amongst low income population, however, this factor did not motivate this group to quit tobacco use. A similar picture could be drawn in the current study as despite of having higher monthly expenditure on tobacco use, subjects made no attempts to quit.…”
Section: Discussionmentioning
confidence: 92%
“…The limited public subsidization of NRT in Australia (only patches are subsidized) may be another reason that fast‐acting NRT products were not suggested to smokers with MI, who may be financially stressed and potentially cannot afford to buy NRT over the counter at full cost (Martire et al . ). Similarly, not receiving prescriptions for subsidized smoking cessation medications such as varenicline or bupropion can be a barrier to quitting smoking for smokers with MI (Tall et al .…”
Section: Discussionmentioning
confidence: 97%